Assessing CO2 Adsorption on Amino-Functionalized Mesocellular Foams Synthesized at Different Aging Temperatures - Vilarrasa-García, Enrique; Cecilia, Juan Antonio; Moura, Pedro Augusto S.; Azevedo, Diana C. S.; Rodríguez-Castellón, Enrique (Frontiers in Chemistry, 2020)
Research groups worldwide investigate different pathways to mitigate CO2 emissions, by capturing them using alternative technologies to current ones with technical and economic advantages. A wide variety of solid sorbents has recently been synthesized for application in CO2 adsorption. Among them, mesoporous silicas deserve attention because of their ability to accommodate large concentrations of different chemicals as a consequence of their surface chemistry and tunable pore structure. Functionalized materials exhibit promising features for CO2 adsorption at high temperatures and low CO2 concentrations. This work aimed to assess the influence of the textural properties on the performance of CO2 adsorption on functionalized mesoporous silica. With this goal, several mesoporous silica foams were synthesized by varying the aging temperature, obtaining materials with larger pore diameter. Thus, the synthesized materials were functionalized by grafting or impregnation with 3-aminopropyltriethoxysilane, polyethylenimine and tetraethylenepentamine as amine sources. Finally, the amino functionalized materials were assessed for CO2 capture by means of equilibrium adsorption isotherms at 25, 45 and 65ºC.